2015
DOI: 10.1007/s11240-015-0823-2
|View full text |Cite
|
Sign up to set email alerts
|

Identification and functional characterization of ten AP2/ERF genes in potato

Abstract: Ethylene-responsive element-binding factors (ERF) constitute one of the largest transcription factor families in plants. In this study, we describe the cloning and the characterization of ten cDNAs encoding ERF factors from potato. The alignment of their AP2/ERF (Apetala2/ethylene-responsive factor) domain led to the identification of six StERFs (Solanum tuberosum ERFs) and four StDREBs (dehydration responsive element binding). The phylogeny and the sequence characterization allowed the classification of these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(9 citation statements)
references
References 108 publications
1
7
0
Order By: Relevance
“…Similar results were also observed in JA‐ and SA‐induced genes, such as IbERF5 and IbERF7 which were upregulated by JA and SA treatments, and were increased by different abiotic stresses. The data are similar to other reports, such as potato StERF3 and StERF6 genes were induced by salt, ABA, JA, and SA treatments (Bouaziz et al., 2015). These findings suggested that multiple IbERF s might participate in JA or SA pathways, and might be involved in the biotic response of sweetpotato.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Similar results were also observed in JA‐ and SA‐induced genes, such as IbERF5 and IbERF7 which were upregulated by JA and SA treatments, and were increased by different abiotic stresses. The data are similar to other reports, such as potato StERF3 and StERF6 genes were induced by salt, ABA, JA, and SA treatments (Bouaziz et al., 2015). These findings suggested that multiple IbERF s might participate in JA or SA pathways, and might be involved in the biotic response of sweetpotato.…”
Section: Discussionsupporting
confidence: 92%
“…Jasmonic acid and SA play crucial roles in the defense response of plants to pathogens and abiotic stress (Bari & Jones, 2009). Multiple studies in potato (Bouaziz et al., 2015), tomato (Sharma et al., 2010), and rice (Sharoni et al., 2011) have shown that some AP2/ERFs could regulate stress response by both ABA‐dependent and ABA‐independent pathways in plants. The expression of seven IbERF s was obviously upregulated by ABA.…”
Section: Discussionmentioning
confidence: 99%
“…The drought‐responsive element binding (DREB) factors comprise a subfamily of the AP2/ERF family of TFs containing single AP2 DNA‐binding domains, which recognize six nucleotides (A/G)CCGAC of the dehydration‐responsive element/C‐repeat (DRE/CRT). These cis ‐elements are located on promoter regions of target stress‐responsive genes and play an important role in regulation of stress‐inducible transcription (Agarwal et al ., ; Bouaziz et al ., ; Hrmova and Lopato, ; Sakuma et al ., ).…”
Section: Introductionmentioning
confidence: 98%
“…So far, a few salt-responsive genes have been identified in potato, such as zinc finger protein gene (StZFP1) 16 ; ethylene-responsive transcription factors (StERF1, StERF3 and StERF6) 17 ; dehydration-responsive element-binding protein genes (StDREB1, StDREB2, StDREB3 and StDREB4) 17,18 . With the development of high throughput sequencing technology, RNA-seq has been more and more frequently used in plant stress resistance research.…”
mentioning
confidence: 99%